Modeling the Interplay between Sanitary and Phytosanitary Measures and Tariff-rate Quotas under Partial Trade Liberalization. (26th August 2016) - Beckman, Jayson; Arita, Shawn
Abstract: Non-tariff measures, particularly sanitary and phytosanitary measures and tariff-rate quotas, are two critical policy barriers that impede agricultural trade. Unlike simple tariffs, both measures contain non-linear effects and binding conditions that make their treatment in modeling trade liberalization challenging. In addition, the coexistence of these measures carries important interactive effects that restrict trade. This study investigates these joint effects by developing a conceptual framework that considers different partial liberalization scenarios. Our framework points to three cases that may arise: ( a ) binding tariff-rate quota, non-prohibitive sanitary and phytosanitary measure; ( b ) non-binding tariff-rate quota, non-prohibitive sanitary and phytosanitary measure; and ( c ) non-binding tariff-rate quota, prohibitive sanitary and phytosanitary measure. We then use a Computable General Equilibrium model to examine partial trade liberalization scenarios for these cases, using the ongoing Transatlantic Trade and Investment Partnership negotiations as our motivation. Our simulations provide a more nuanced analysis of complex trade liberalization and demonstrate the importance of modeling the interplay between these different types of barriers.